The Impact of Waste Management and Application of the 3R Method in theMajalengka Heuleut Landfill as a Supplement to Environmental Pollution Material - Muhamad Kurnia Sugandi; Margareta Rahayuningsih; Aditya Marianti (Universitas Negeri Semarang, 2025)
Waste is one of the most common environmental problems, including organic and inorganic waste that is often found around settlements. The Heuleut Landfill in Majalengka Regency, West Java, has a problem of waste accumulation that exceeds its capacity, causing negative impacts on the environment and the health of the local community. The volume of waste is estimated to be more than 100 tonnes per day, with an average of about 0.7 kg of waste per person per day. This research used a descriptive qualitative approach, collecting primary data through field observations and interviews, and secondary data through document analysis. The research findings show the significant impacts of the Heuleut landfill management, including soil, water and air pollution, which affect health and agricultural yields. The results of the analysis were used as a supplement to the ecology course. The students' positive response to waste management reflects an increased level of environmental awareness. Waste management through the 3Rs (Reduse, Reuse, Recycle) method, such as the production of briquettes, pulp and compost, as an alternative to environmentally friendly waste management was presented to the students using interactive Flash Player applications to enhance their understanding. In conclusion, better waste management is needed so that Heuleut Landfill does not only function as a final disposal site, but also plays an active role in waste management by applying the principles of the 3R's. This is an important step in maintaining environmental sustainability and the welfare of the local community.